Effects of Utilization of Mass Media (Video) in the Academic Performance Children At Risk Due To Pandemic in Grade 2 Pupils of Tayuman Elementary School - OCAMPO, FELIPE (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Mass media denotes a section of the media designed to reach a large audience. It can be referred to as a means of public communication such as television, radio and widely circulated newspapers that tend to reach a large audience with similar social characteristics (Mintz, 2015). Thompson (2014), defined mass media as books, magazines, newspapers, radio, television, cinemas, records, tapes and videos. Mass media is as communication media that reach a large audience, especially television, radio and newspaper. Media can be defined broadly as channels of communication. It is considered in terms of its software and hardware (Ogunmilade, 2014). This study therefore hopes to explore the effects of the mass media specifically video lessons on the performance level of the children at risk in Grade 2 coming from different sections of Tayuman Elementary School (TES) This study has 23 respondents who are the children at risk of dropping out from all the sections of Grade Two. These pupils may fail or drop from the school due to their reasons some of which are uncontrolled. The researcher used the tabulated individual average results of the LOA for the second quarter as the initial basis of the study. The second question was taken from the LOA average results of the 23 pupils who were given the intensive intervention using the video lessons apart from the SLMs and other tasks which they accomplished for the Third quarter. The researcher then compared the LOA results after the intervention sessions using video lessons vis a vis before where the pupils did not undergo any intervention. Then the results were tabulated by the researcher to identify the effects of the intervention administered to the pupils. Whether the variable of stopping or dropping out from the school in controllable or not, the researcher used one of the mass media which is video lessons in conducting intervention to these pupils. The video lessons are from the Marungko booklet which is modified by the Grade One teachers of Tayuman Elementary School. This experimental study was carried out to show the effects of watching videos/video lessons in the performance of the selected Grade 2 pupils at risk of dropping out and failure. The finding gave positive results and the videos found out to be beneficial in child’s learning to read and comprehend. Videos help learners put together the ideas of every watching experience.